Islamophobia in American Against Muslims in “My Name is Khan” Film - Rahim, Amirah Asmaniar Muslimah; Nur, Muh Safar; Halim, Abd. (KARIWARI SMART : Journal of Education Based on Local Wisdom, 2024)
This research discusses Islamophobia that occurs in America in the film "My Name is Khan". The purpose of this study is to find the main causes and consequences of the emergence of Islamophobia in America in the film "My Name is Khan" from various aspects using the theory of Bunzl and Matti (2007). The researcher found two main causes of the emergence of Islamophobia in America, namely physical violence and prejudice. The author also found various consequences of the emergence of Islamophobia in three main aspects, namely social, economic, and psychological. This research uses a qualitative method where the data does not contain numbers and is taken from written and spoken data. The results of this study found that the most common cause of the emergence of Islamophobia is dominated by prejudice which is the main driver of the emergence and spread of Islamophobia in America with the most consequences found in the social aspect.